ANTIOXIDANT ACTIVITY AND INHIBITION OF LIPOXYGENASE ACTIVITY ETHANOL EXTRACT OF ENDOSPERM ARENGA PINNATA (WURMB) MERR. - Elya, Berna; Puspitasari, Nuraini; Sudarmin, Annisa Chairani (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The purpose of this study is to determine the antioxidant activity and the potential inhibition of lipoxygenase activity from sugar palm fruit. Methods: Antioxidant activity was evaluated by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) methods. Inhibition of lipoxygenase activity was performed in vitro. Sugar palm fruit was macerated with 95% ethanol. Results: The results showed that sugar palm fruit ethanol extract has antioxidant activity when using DPPH method with EC50 of 141.3929 Î¼g/mL and the FRAP method with EC50 of 60.2083 Î¼g/mL. Inhibition test of lipoxygenase activity showed inhibitory concentration 50% value of 71.376 Î¼g/mL. Conclusions: Ethanol extract of endosperm Arenga pinnata has antioxidant activity, as determined using the DPPH method with EC50of 141.3929 Î¼g/mL and the FRAP method with EC50 of 60.2083 Î¼g/mL.